A case series of peripheral nerve blocks in pediatrics and young adults with skeletal dysplasia. Issue 5 (21st March 2016) - Eiszner, James R.; Atanda, Alfred; Rangavajjula, Ashwin; Theroux, Mary
Summary: Aim: The purpose of this study was to report our experience with peripheral nerve blockade in pediatric and young adult patients with skeletal dysplasia undergoing knee arthroscopy. Background: The incidence of skeletal dysplasia is 1 : 4000 live births. These patients have biomechanical predispositions to knee joint degeneration, which is often palliated by arthroscopic surgery. Regional anesthesia has been proven to improve the cost and quality of care in adults undergoing arthroscopic knee surgery. Methods: This was a retrospective case series of patients with skeletal dysplasia undergoing arthroscopic knee surgery from 2012–2014 at a tertiary‐care, pediatric hospital. Data pertaining to block effectiveness, technique, adjunct local anesthetic, rates of postoperative nausea/vomiting and admissions, and complications were recorded. Results: Twenty patients with skeletal dysplasia underwent arthroscopic knee surgery during the study period. Ten of these patients received peripheral nerve blockade (12 procedures). All patients received femoral, femoral/sciatic, or femoral/sciatic/obturator blocks. One patient required opioid, constituting a block failure. The same patient required overnight admission for pain control. No patients suffered from PONV. There were no complications associated with any of the blocks performed. Conclusions: Patients with skeletal dysplasia receiving lower extremity nerve blocks consume minimal opioid and report no major complications. Anesthesiologists should consider this mode of anesthesia in these patients. While no nerve injuries were discovered, further study is necessary to determine whether rates of nerve injury are comparable to that in the general pediatric population. Given the size of the skeletal dysplasia population, this type of study would require close to a decade of metadata from numerous institutions. Abstract :